The dental workforce in Malaysia: drivers for change from the perspectives of key stakeholders. (31st May 2020) - Che Musa, Muhd Firdaus; Bernabé, Eduardo; Gallagher, Jennifer E.
Abstract : Objective: The dental workforce is facing unprecedented change globally as a result of multiple influences. There is a need for research informed action to map possible drivers for change at the national level and examine their potential implications in order to shape the dental workforce to serve population needs. The objective of this study was to explore key stakeholders' views on the drivers for change for the Malaysian dental workforce and their potential implications. Method: Stakeholders from key dental organisations/professions in Malaysia were purposively sampled and invited to participate in a semi‐structured interview ( n = 20) using a pre‐tested topic guide. Interviews were recorded, transcribed verbatim and analysed using Framework Analysis. Results: Drivers for workforce were identified across four main domains: policy‐politics; trends in demography; social and economic; and, technology‐scientific development. The pace of change and possible interplay between drivers, most notably government policy, liberalisation of education and health services and challenges of workforce governance, followed by Malaysian demography and health trends. Implications for the future, including possible uncertainties, particularly in relation to specialisation and privatisation were identified, together in balancing and meeting public health needs/demands with professional career expectations. Conclusion: Stakeholders' views on the high‐level drivers for change broadly mirror those of high‐income countries; however, specific challenges for Malaysia relate to rapid expansion of dental education and a young workforce with significant career aspirations, together with imbalances in the health care system. The impact of these drivers was perceived as leading to greatest uncertainty around specialisation and privatisation of the future workforce.